Thelma Nord, Library Trustee New Mexico Library Association Newsletter - Lloyd, Betty (New Mexico. New Mexico Library Association, 1975)
Article written by Ms. Lloyd about Thelma Nord in her role as a library trustee. Located in the NMLA newsletter dated December 1975
Article on Thelma Nord located in newsletter page 3
Master list item # 12
File location is in the Raton File Cabinet drawer 3
Keywords: Nord, Thelma -- Library trustee; Llyod, Betty -- Librarian; Library. -- Raton, New Mexico; NMLA newsletter; Library Trustees -- Arthur Johnson Memorial Library; Library Boards -- Arthur Johnson Memorial Library; Raton, New Mexico